Ghana - 2007 External Review of Public Financial Management : Volume 2. Public Procurement Assessment Report - World Bank (Washington, DC, 2012)
The 2007 External Review of Public Financial Management (ERPFM) is the fourth in a series of annual assessments by the development agencies that contribute to the Multi-Donor budgetary support in Ghana. The 2007 ERPFM review has four main findings: 1) the progress in strengthening the Public Financial Management (PFM) system has been commendable. 2) In order to address the drivers of additional public spending in 2006 and 2007 as well as increase the effectiveness of public investment, attention now should focus on high return actions, such as: (i) completing the implementation of the Integrated Personnel and Payroll Database (IPDD2) and other measures aimed at reasserting control over the wage bill; (ii) ensuring continued reduction in energy subsidies through alignment of tariffs with current market conditions, including the international oil market prices; and (iii) the building of capacity to prepare, appraise and implement large infrastructure projects, especially now that the Government is preparing for a major infrastructure investment drive. 3) A strong foundation has been laid for open, competitive and transparent public procurement and a major effort is underway with a view to building understanding of the new system and capacity to manage it. 4) The successful launch of the Ghanaian Eurobond provides the opportunity to reduce the Government's exposure to the domestic bond market, and restore the virtuous cycle of lower public sector indebtedness that was initiated in 2003 with reduction in domestic debt, declining inflation and domestic real interest rates, and rising public and private investment. The External Review of Public Financial Management (ERPFM) on these key findings, first, it covers recent economic performance and outlook and then reviews issues related to the pattern of public spending. After reporting on progress in strengthening public financial management, it summarizes findings of the public procurement assessment. The detailed findings of the public procurement assessment constitute volume two of the 2007 ERPFM. At the end the ERPFM proposes to focus on in the short and medium-term and the baseline scores of Ghana's public procurement system for each of the 54 sub-indicators covered by the Organization for Economic Co-operation and Development - Assistance Committee (OECD-DAC) methodology, respectively.